Assessment of Vitamin D Status in Pregnant Women, a Prospective Observational Study from Northern District of Kashmir Valley (Academia Journal of Medicine, 2019)
Background: An increased prevalence of vitamin D deficiency has been reported from across the globe including India. Various studies have shown an intrinsic relation between various parameters of maternal and fetal wellbeing with maternal vitamin D status during pregnancy.  Aims: To prospectively assess the vitamin D nutritive status in pregnant women in North district of Kashmir Valley and to study the  prevalence of suboptimal vitamin D status in apparently healthy pregnant North Kashmiri women.Study Design: Sixty three consenting  pregnant women attending the antenatal clinic of the DH Baramulla and Endocrine OPD over the study period of 12 months were enrolled. Subjects and Methods: The subjects underwent a detailed history and physical examination as per a pre-formed Performa. History was  focused on occupation, dietary history including diet taken in last 24 hours, exposure to sunlight, drug intake, menstrual history and history of  any systemic illness. A particular record was made of the women’s dressing habits. Of the 63 subjects recruited, only 60 subjects (in whom  Vitamin D levels could be estimated) were further analyzed for the study. Serum levels of [25 (OH) D] were estimated by 25-OH-D assay, an  RIA based procedure. Results: In the present study, vitamin D insufficiency (defined as serum 25[OH] D levels
Keywords: Vitamin D; Pregnancy